Mig‐6 could inhibit cell proliferation and induce apoptosis in esophageal squamous cell carcinoma. Issue 1 (30th November 2021) - Cui, Yuantao; Kang, Ying; Zhang, Peng; Wang, Yuanguo; Yang, Zhaoyu; Lu, Chao; Zhang, Peng
Abstract: Background: To investigate the expression and biological functions of mitogen‐induced gene 6 (Mig‐6) in esophageal squamous cell carcinoma (ESCC). Methods: The expression of Mig‐6 in ESCC tissues and normal esophageal epithelial tissues were measured by immunohistochemistry (IHC) assay. MTT test was applied to detect the proliferative ability of ESCC cells after Mig‐6 was upregulated by transfection. A fluid cytology assay was used to detect apoptosis of ESCC cells. Agilent whole human genome oligo microarray was used to screen different expressed genes and the possible signaling pathways which might be involved. Results: The expression of Mig‐6 protein was lower in ESCC tissues compared to normal esophageal epithelial tissues. Mig‐6 could restrain the ESCC cell growth and induce cell apoptosis. PPAR, CAMs and MAPK signaling pathways might be involved. Conclusions: Mig‐6 might be a new tumor suppressor gene and a possible target for the specific therapy of ESCC. Abstract : The expression of Mig‐6 protein was lower in ESCC tissues (a, b) compared to normal esophageal epithelial tissues (c, d). Mig‐6 could restrain the ESCC cell growth and induce cell apoptosis. PPAR, CAMs and MAPK signaling pathways might be involved in it. Mig‐6 might be a new Tumor Suppressor Gene and a possible target for the specific therapy of ESCC.